Clinical laboratory diagnosis of obstructive megaureter in children - Svekatun, V. N.; Dmitryakov, V. A.; Lytvynenko, O. S.; Свєкатун, Вячеслав Миколайович; Дмитряков, Валерій Олександрович; Литвиненко, Олена Семенівна (My University, 2020)
Introduction. Currently, there are more than 200 methods of surgical treatment of a megaureter, but none of the methods has achieved universal acceptance. Until now, the issues of differential diagnosis of organic and functional causes of ureteral dilatation in children under 3 years of age have not been sufficiently illuminated, there is no generally accepted algorithm for the management of patients with this pathology. Relevance. The relevance of obstructive uropathies is evidenced by the fact that they occupy the third position in the list of the most common causes of chronic kidney disease in children, and account for 15% of cases. The prognosis of the outcome of obstructive uropathy is determined by the nature of the lesion and the degree of involvement in the pathological process of the kidneys, one of the main homeostatic and endocrine organs in humans. The degree of involvement of various markers in the development and progression of kidney damage in children is still insufficiently understood. All this prompts the search for screening, highly sensitive and specific methods for the diagnosis and prediction of nephrosclerotic changes in children against the background of urinary tract obstruction. Objective: The study of the clinical and laboratory diagnostic methods, allowing to differentiate functional or organic urodynamic disorders, to determine the tactics of managing patients with obstructive uropathy.
Keywords: obstructive megaureter; cystatin C; stenting; ureter; children